2022
DOI: 10.1128/spectrum.02080-21
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Breast Milk Microbiome in the Early Postpartum Period of Kenyan Women Living with HIV Are Influenced by Antibiotics but Not Antiretrovirals

Abstract: Breastfeeding has important benefits for long-term infant health, particularly in establishing and shaping the infant gut microbiome. However, the impact of combination antiretroviral therapy exposure and antibiotics on the breast milk microbiome in women living with HIV is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
3
4
0
Order By: Relevance
“…Unlike previous studies that mostly included patients from China, our study included Kenyan participants, infants, and women living with HIV. Another nding consistent with other studies was the association between antibiotic use signi cant dissimilarity in bacterial beta diversity among women [55][56][57] . Additionally, we found that both HIV and SARS-CoV-2 have impact on the gut microbiome as has been found in previous studies 8, 17,18,20,58,59 .…”
Section: Discussionsupporting
confidence: 89%
“…Unlike previous studies that mostly included patients from China, our study included Kenyan participants, infants, and women living with HIV. Another nding consistent with other studies was the association between antibiotic use signi cant dissimilarity in bacterial beta diversity among women [55][56][57] . Additionally, we found that both HIV and SARS-CoV-2 have impact on the gut microbiome as has been found in previous studies 8, 17,18,20,58,59 .…”
Section: Discussionsupporting
confidence: 89%
“…The relative abundances of these dominant genera changed over time, with Staphylococcus declining in abundance while Streptococcus and Veillonella increased. This is similar to the trajectory in breastmilk microbiota composition reported in Kenya [ 26 ]. The infant salivary microbiota is known to be colonized by Streptococcus [ 27 , 28 ], such that the continued dominance of Streptococcus in maternal breastmilk may partly reflect breastmilk-saliva interplay.…”
Section: Discussionsupporting
confidence: 88%
“…The relative abundances of these dominant genera changed over time, with Staphylococcus declining in abundance from week 1 of life onwards, while Streptococcus and Veillonella increased in abundance. This is similar to the trajectory in breastmilk microbiota composition reported in Kenya [26]. The infant salivary microbiota is known to be colonised by Streptococcus [27,28], such that the continued dominance of Streptococcus in maternal breastmilk may partly reflect breastmilk-saliva interplay throughout early life.…”
Section: Discussionsupporting
confidence: 80%